Analyzing Budget Efficiency Policies in Strengthening Disaster Management Performance in Riau Islands Province - Sartika Effendhy, Dewi; Subiyakto, Rudi; Okparizan, Okparizan (Jurnal Sains Sosio Humaniora, 2026)
The 2025 budget efficiency policy implemented by the Indonesian government through Presidential Instruction Number 1 of 2025 has influenced regional financial management, including the Regional Disaster Management Agency (BPBD) of Riau Islands Province. This study aims to analyze the budget efficiency policy in supporting BPBD performance and examine its impact on disaster preparedness and emergency response capacity. This research employed a qualitative descriptive approach. Data were collected through interviews, observation, documentation, and literature studies. The analytical framework used William N. Dunn’s policy analysis theory, consisting of problem structuring, forecasting policy outcomes, policy recommendation, monitoring policy outcomes, and policy evaluation. The findings indicate that the budget efficiency policy successfully reduced regional expenditures; however, it also affected operational spending, logistics readiness, and disaster response capacity. Budget reductions in goods and services expenditure and capital expenditure limited BPBD’s operational effectiveness in disaster management. The efficiency policy was more focused on expenditure reduction rather than optimizing disaster management priorities. Consequently, disaster preparedness, logistics availability, and institutional capacity experienced significant constraints. This study recommends the implementation of performance-based budgeting, disaster risk-based budget prioritization, and stronger inter-agency coordination to improve disaster management governance in Riau Islands Province